Proteomic analysis reveals GMP synthetase as p53 repression target in liver cancer - Holzer, Kerstin; Drucker, Elisabeth; Rössler, Stephanie; Waldburger, Nina; Eiteneuer, Eva; Herpel, Esther; Breuhahn, Kai; Schirmacher, Peter; Singer, Stephan (The American journal of pathology, 2017)
Disruption of the tumor-suppressive p53 network is a key event in human malignancies, including primary liver cancer. In response to different types of stress, p53 mediates several antiproliferative cellular outcomes, such as cell cycle arrest, apoptosis, and senescence, by activation or repression of its target genes. Metabolic alterations initiating or being part of the p53 response have become an actively studied research area in the p53 field, with several aspects that still remain to be elucidated. Herein, we identified GMP synthetase (GMPS), a key enzyme of de novo purine biosynthesis, as an important p53 repression target using a large-scale proteomics approach. This p53-mediated repression of GMPS could be validated by immunoblotting in Sk-Hep1, HepG2, and HuH6 cells. Moreover, we found GMPS transcriptionally repressed in a p21-dependent manner and its repression maintained in the context of p53-mediated cellular senescence. More important, direct knockdown of GMPS by RNA interference resulted in reduced cell viability and was sufficient to trigger cellular senescence. Finally, by comparing murine hepatocellular carcinomas, which developed in p53 wild-type (+/+) versus p53 null (−/−) mice, we observed higher GMPS expression in the latter, supporting the in vivo relevance of our findings. We conclude that repression of GMPS by p53 through p21 is a functionally relevant part of the p53-mediated senescence program limiting tumor cell growth in liver cancer.